Karakteristik Klinis Glaukoma Uveitis di Pusat Mata Nasional Rumah Sakit Cicendo Bandung Tahun 2021-2022 - Andrianto, Refandi Dwi; Gustianty, Elsa; Rifada, Raden Maula (Jurnal Kesehatan Andalas, 2023)
Uveitic glaucoma is a complication of uveitis that can occur due to severe intraocular inflammation. Objective: To determined the clinical characteristics of uveitic glaucoma based on clinical features and management at the Cicendo Hospital National Eye Center from 2021 until 2022. Methods: This study used a retrospective descriptive method and a cross-sectional design with secondary data as subjects in the form of electronic medical records of patients at the National Eye Center Cicendo Hospital Bandung who had a diagnosis of uveitic glaucoma in the period January 2021 until December 2022. Results: 162 patients (228 eyes) met the inclusion criteria. Most of the patients were women, with a percentage of 66%. Anterior uveitis (44.3%) was the most common type of uveitis. The mean IOP at the initial visit was 30.1 mmHg. One hundred fourteen eyes (50%) were below 3/60 visual acuity. Infection (41.4%) was the most common cause of uveitis. A total of 107 eyes (46,9%) underwent surgery. There was a decrease in the average IOP in each follow-up period. Conclusions: Glaucoma uveitis is commonly found in women with an average age of 48.6 years. Anterior uveitis with an infectious cause is the most common type and cause of uveitis. The most common surgery is a combination of trabeculectomy, lens extraction, and IOL implantation.Keywords: Â management of glaucoma, Â secondary glaucoma, uveitic glaucoma